Physical fitness and habitual level of physical activity associated with cardiovascular health in adults and elderly - Trapé, Átila A.; Lizzi, Elisangela A.S.S.; Jacomini, André M.; Hott, Sara C.; Bueno, Carlos R.; Zago, Anderson S. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2015)
Study design: Cross-sectional Background: The habitual level of physical activity (HLPA) has been used to establish the relation between active lifestyle and cardiovascular health. However, the assessment of physical fitness would review the actual physical condition of the individual, and thus can have better relations with cardiovascular health. Objectives: Relate HLPA and physical fitness with cardiovascular health of adults and elderly and to verify the association of supervised regular physical exercise with different levels of fitness. Method: 213 adults and elderly (> 50 years) participating in community projects were evaluated. The HLPA were assessed by the IPAQ and physical fitness through a battery of motor tests that allowed the calculation of the General Functional Fitness Index (GFFI). Blood pressure, lipid profile and body mass index were considered as indicators of cardiovascular health. Results: The generalized linear model showed a greater number of differences with respect to variables related to cardiovascular health when participants were subdivided having GFFI as an independent variable, compared to HLPA. The Fisher exact test showed that the groups GFFI classified as good and very good showed a higher proportion of individuals with regular practice for more than 6 months exercise, especially for a larger number performing the practice under supervision (p <0.0001). Conclusion: The GFFI has better association with cardiovascular health than HLPA and time of practice and supervision are associated with the level of physical fitness.
Aptidão física e nível habitual de atividade física associados à saúde cardiovascular em adultos e idosos
Keywords: Aging; Cardiovascular Diseases; Exercise; Motor Activity; Physical Fitness